Enhanced Surveillance for Meningococcal Disease-United States, 2015-2019. - Amy B Rubis; Daya Marasini; Rebecca Howie; Basanta Wagle; Shalabh Sharma; Brittney Thomas; Sara Eisen; Sandip Shrestha; Henju Marjuki; Lucy A McNamara (PLoS ONE)
Background High quality surveillance data are important to monitor U.S. epidemiology of meningococcal disease. Enhanced Meningococcal Disease Surveillance (EMDS) was established in 2015 to collect additional data and isolates from reported cases. Methods Epidemiologic information and isolates obtained through EMDS for meningococcal disease cases reported through the National Notifiable Diseases Surveillance System (NNDSS) during 2015-2019 were included in the analysis. Isolates were characterized by serogrouping and molecular typing using either Sanger sequencing or whole genome sequencing. Case fatality ratios (CFRs) were calculated using cases with known outcome as the denominator. Odds ratios (ORs) were calculated using logistic regression. Results A total of 1,806 meningococcal disease cases were reported during 2015-2019. The average annual incidence was 0.11 cases per 100,000 population. For key variables already collected through NNDSS, EMDS improved completeness over NNDSS by 21%-39% each year during 2015-2019. Completeness of key variables in EMDS improved over time by an average of 18%. Testing of isolates submitted through EMDS showed that serogroups B and C were predominant in all five years. For serogroup B, the most common clonal complex (CC) was CC32 in 2015-2017 and CC41/44 in 2018-2019; for serogroup C, CC11 was most common in 2015-2017 and CC103 in 2018-2019. The CFR was significantly lower for CC103 (6.7%) compared to other CCs (13.6%) (OR 0.44, 95% CI: 0.22-0.89). Conclusions U.S. incidence of meningococcal disease remained low during 2015-2019. Data and isolates obtained from EMDS supplement NNDSS and are critical to monitor U.S. meningococcal disease epidemiology.